Measuring the Quality of Legal Aid Services as the Embodiment of Access To Justice - Oki Wahju Budijanto; Tony Yuri Rahmanto (Badan Strategi Kebijakan Hukum, 2022)
Since the enactment of Law Number 16 of 2011 concerning Legal Aid, the practice of legal aid services still has several problems including not being able to reach all districts/cities due to the limited number of Legal Aid Organizations that can provide services. This paper aims to describe the implementation of legal aid services and analyze optimal strategies in improving the quality of legal aid services. This study used two approaches, qualitative and quantitative or commonly referred to as the Mix Method. Data collection methods used in this study are surveys, interviews and document studies. The results of the study show that the quality of legal aid services as a manifestation of access to justice can be said to be very good by referring to the results of the assessment on the performance of legal aid organization units and the quality of litigation and non-litigation legal aid services. However, several aspects need attention, namely the information aspects in litigation services and the procedural aspects of non-litigation services. Guided by the results of the study, a strategy is needed to improve the quality of legal aid organization services by increasing access to information to service recipients. Legal Aid providers can use online surveys in evaluating the implementation of legal aid services throughout Indonesia. This strategy is the right step, effective, efficient and in accordance with the pandemic conditions and technological advances.